Концептуальні основи організаційно-економічного регулювання продовольчого ринку - Ібатуллін, Марат Ільдусович; Трусова, Наталя Вікторівна; Гривківська, Оксана Василівна (My University, 2023)
Особливістю сучасного етапу розвитку організаційно-економічної системи продовольчого забезпечення країни є подолання стримуючих факторів, вплив яких можна контролювати за допомогою цілеспрямованих дій на процеси її становлення. Подібні заходи на національному й регіональних рівнях слід реалізувати у рамках концепції розвитку системи продовольчого забезпечення, яка передбачає: обґрунтування цілей, завдань і параметрів продовольчої системи; визначення обсягів потреби в продовольчих ресурсах; перспективи територіального розміщення виробництва сільськогосподарської продукції, її переробки та доведення до рівня продовольчих ресурсів. Abstract Introduction. A feature of the modern stage of development of the organizational and economic system of the country's food supply is the overcoming of restraining factors, the influence of which can be controlled with the help of purposeful actions on the processes of its formation. Similar measures at the national and regional levels should be implemented within the framework of the concept of development of the food supply system, which provides for: substantiation of the goals, tasks and parameters of the food system; determining the amount of need for food resources; prospects for the territorial placement of agricultural production, its processing and bringing it up to the level of food resources. Goal. On the basis of the conducted research, propose recommendations for improving the conceptual foundations of the organizational and economic regulation of the food market. Method (methodology). To implement the tasks, the following methods and techniques were used: monographic, comparison - to compare economic phenomena in different time periods in order to identify a cause-and-effect relationship, to conduct a comparative analysis of the development of the food market; abstract and logical - when substantiating hypotheses regarding the production and consumption of agricultural products and food. Results. It has been proven that the practical implementation of conceptual approaches to the organizational and economic regulation of the food market is possible only under the condition of creating an appropriate system of strategic management and operational tactical adjustment of the implementation of the decisions made. This requires the creation of such an organizational and economic mechanism that will take into account the specifics of industries, the variability of factors that determine economic dynamics and market conditions, and will have the following main blocks: financial and economic, organizational and informational, personnel and legal.
Keywords: кафедра економіки і права; моніторинг; продовольчий ринок; попит; пропозиція; ціна; регулювання; концепція; продовольчі ресурси; сільськогосподарська продукція; regulation; food market; concept; food resources; agricultural products